Potentially Toxic Elements’ Accumulation and Health Risk of Consuming Vegetables Cultivated along the Accra-Tema Motorway - Ebenezer Boahen; Benedicta Yayra Fosu-Mensah; Samuel S. Koranteng; Daniel A. Darko; Gerald Obuobi; Michael Mensah (Journal of Chemistry)
Vegetables cultivated close to highways have the potential to accumulate potentially toxic elements (PTEs), either through uptake from contaminated soil or via atmospheric deposition from vehicular emissions, and pose health risks when ingested by humans. The study investigated the concentrations of chromium (Cr), zinc (Zn), nickel (Ni), copper (Cu), cadmium (Cd), manganese (Mn), and iron (Fe) in lettuce (Lactuca sativa), African eggplant (Solanum melongena), and jute leaves (Corchorus olitorius) at distances 0–10, 50, and 200 m and the health risk of consuming these vegetables. Vegetable samples were digested using an automated digester, Behrotest model K8, and levels of potentially toxic elements were analyzed using an atomic absorption spectrophotometer (AAS) PinAAcle 900T. The mean element concentrations investigated in the three vegetables exceeded the WHO/FAO recommended limits except for Cu and Mn concentrations. The estimated mean concentrations of potentially toxic elements in the vegetables decreased with increasing distance from the edge of the road except for cadmium concentrations in African eggplant and chromium concentrations in jute leaves at 50 and 200 m distances. The estimated hazard index (HI) of potentially toxic elements in the vegetables in both children and adults was greater than 10 (HI > 10) and hence poses a possible health risk if ingested. The HI values for the various elements decreased with increasing distance from the edge of the road in lettuce and jute leaves, except for African eggplant, where the HI values increased with increasing distance from the edge of the road. Of the seven PTEs investigated, Cd, Cr, and Ni contributed the most to the overall HI in all the vegetables. It was further observed that the carcinogenic risk (CR) and total carcinogenic risk (TCR) for chromium and cadmium in the vegetables exceeded the threshold level of CR > 10−6 and TCR > 10−4 except for the cadmium value found in African eggplant at 200 m from the road. It is therefore recommended that the cultivation of vegetables along the highway should be halted as these vegetables pose potential health risks when consumed.